The Development of Teaching Materials of Reading Comprehension Using the Big Question Strategy at Indonesian Language and Literature Students - Eddy Pahar Harahap; Andiopenta Purba; Yusra D; Dudu Mawarida Sembiring; Akhyaruddin Akhyaruddin (AL-ISHLAH: Jurnal Pendidikan, 2023)
Reading comprehension is one of the important activities to gain knowledge, information, or to get entertainment. The research aims to produce teaching materials for reading comprehension skills that are valid, practical, and effective. This type of research is development research with the Plomp development model developed by Tjeerd Plomp, 2010. The research subjects were 48 fifth semester students. The results showed that reading comprehension teaching materials used the big question strategy for Indonesian language and literature education students with valid, practical, and effective categories with a percentage of 90%. It is concluded that the use of teaching materials for reading comprehension skills using the big question strategy is feasible to use.